Audiens Milenial dan Iklan Viral: Kajian Daya Tarik Iklan #KerenLahirBatin terhadap Brand Image Ramayana Department Store - Hasna Nur Lina; Lidwina Mutia S (Jurnal Media dan Komunikasi Indonesia, 2020)
Advertising appeals as one of advertising aspects to attract target audiences is significant to be analyzed, furthermore advertisements that audiens consume are excessive day by day. Ramayana Department Store as one of Indonesian mature vendor are catching up with the dynamics by developing advertising appeal that they have. One of the innovative efforts that they done is Ramadan advertising entitled #KerenLahirBatin that going viral in 2018 with more than 12 million times watched and 9,806 comments until by the end of 2018. This research is focusing on describing the effect of advertising appeals to Ramayana’s brand image using survey methods and descriptive analysis technique. Respondents of this study are Indonesian millennial audiences aged 19-34 years with a sample of 100 people obtained through Slovin’s formula. Finding shown that advertising appeals that bridged by audience involvement in message processing has a greater and positive influence on the brand image of Ramayana Department Store compared to the direct influence of advertising appeals on the brand image that does not including audience involvement. The advertising appeals, especially emotional appeals, are proven to increase motivation, opportunity, and the ability of the audience to watch as well as understand the ad. The dominance of this emotional appeals results in respondents tend to use peripheral route to process messages. However, the results of the formed brand image of Ramayana are positive and are a combination of functional and emotional aspects that are absorbed simultaneously. Noting that the effects generated through peripheral processing route are usually temporary and the effect of advertising appeals and audience involvement are only 16%, other aspects of marketing communication efforts are needed in order to strengthen the brand image of Ramayana Department Store.